Blockchain oracles for decentralized agricultural insurance using trusted IoT data - Manoj T; Krishnamoorthi Makkithaya; Narendra V. G.; Vijaya Murari T (Frontiers in Blockchain)
Agricultural insurance is one of the formal and reliable risk management instruments to cope with agrarian risks. Presently, agricultural insurance products rely heavily on centralized systems that lack transparency and traceability, leading to suboptimal risk assessment and delays in payouts. To address these concerns the fintech industry has started to embrace a popular decentralized technology called blockchain. However, blockchain operates as a deterministic and synchronized state system, which means it cannot directly access real-world data for decentralized applications. A mechanism called oracle is required for the trusted access of agricultural risk factor data to smart contracts from external sources such as Internet of Things (IoT) devices, web services and databases. Hence, the present study proposes a blockchain-based AgriInsureDON framework with a privacy-preserving decentralized oracle for risk factor data access from trusted IoT devices for agricultural insurance. Initially, a method for computing the direct reputation score of IoT devices based on behavioral and data reputation is illustrated. Next, a privacy preserved decentralized oracle mechanism is designed and implemented using a masked secret sharing and secure aggregation scheme. Later, we demonstrate the working of weather-indexed insurance contracts based on decentralized oracle. Finally, a performance analysis of smart contract transactions w.r.t average latency, throughput, average CPU utilization and total memory usage is conducted on Ganache and Sepolia test networks. The evaluation results of privacy-protected decentralized oracle and an indexed insurance contract within AgriInsureDON framework confirms that transactions are efficient and scalable to meet the requirements of expedited claim settlement.